The Language of Learning: Exploring How Family and Instructional Communication Drive English Education Context - Ulfah, Yetty Faridatul; Alhasbi, Faruq; Bachtiar, Farchan (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
Existing studies insufficiently addresses the combined impact of family and instructional communication on English learning motivation among eleventh graders. This study aims to cover this overlooked area by looking into how these types of communication, along with what students intend to learn, impact their motivation to learn English. The study involved 130 participants who were eleventh-grade students at SMA AL Islam 1 Surakarta. Purposive sampling was utilized, with the use of the Slovin formula. The data were analysed by applying the Smart-PLS application to conduct variance-based structural equation modelling (SEM). The research findings indicate that family communication impacts students' interest in learning, shown by the p-value at a level below 0.05, and the t-statistic (4.527) with a coefficient of 0.284. However, family communication does not appear to have an effect on their English learning motivation shown by the failure to meet the p-value requirements of more than 0.05, and the t-statistics (0.676) is not greater than the t-table with a coefficient of only 0.042. These data showed family communication boosts learning interest but not directly English learning motivation. Teacher instruction increases interest without directly affecting motivation. Learning intention acts as a vital mediator, linking communication efforts to motivation enhancement. The study highlights the intricate roles family and teacher communications play in motivating English learning, primarily through the mediating effect of learning intentions. It suggests the need for holistic approaches to study and improve educational strategies for motivation.